Quercetin ameliorates tunicamycin‐induced endoplasmic reticulum stress in endothelial cells - Suganya, N. (Cell Prolif, 2014)
OBJECTIVE: Endothelial dysfunction highlights that it is a potential contributor in the pathogenesis of vascular complications arising from endoplasmic reticulum stress (ER stress) and has been emerging as a main causative factor in vascular failure. Here, we hypothesize that the natural flavonoid, quercetin plays an effective role in reducing ER stress in human umbilical vein endothelial cells. MATERIALS AND METHODS: Human umbilical vein endothelial cells were pre‐treated with different concentrations of quercetin (0–100 μm) before inducing ER stress using tunicamycin (TUN) (0.75 μg/ml); cytotoxicity was assessed by MTT assay. Expression levels of ER stress responsive genes, antioxidant enzymes and apoptotic markers were assessed by qRT‐PCR, while roles of caspase‐3 and PARP cleavage were measured by western blot analysis. RESULTS: Quercetin pre‐treatment at 25 and 50 μm had a cytoprotective effect on cells against TUN‐induced toxicity. Quercetin administration modulated expression level of ER stress genes coding for glucose‐regulated protein 78 (GRP78) and C/EBP‐homologous protein (CHOP), and antioxidant enzymes such as superoxide dismutase and catalase, along with free radical generation assessed by malondialdehyde assay. Induction of apoptosis was prevented with reduction in expression level of Bax, and concomitant increase in Bcl‐2 levels, thus proving its potential against ER stress. CONCLUSION: The current study indicates that quercetin modulated stress responsive genes GRP78 and CHOP, helping endothelial cells prevent TUN‐induced ER stress.